FOSTERING BICYCLING CULTURE IN THE INSTITUTIONAL POLICY PLANNING OF CITIES - Leandro Dri Manfiolete Troncoso; Rodolfo Franco Puttini; Giuliano Gomes de Assis Pimentel; Tony Honorato; Sérgio Alejandro Toro-Arévalo (Journal of Physical Education)
ABSTRACT The objective this research understand perspective of cycloactivists South Region of Brazil in the promotion biciculture in their respective territories. We interviewed six cycloactivists with inclusion criteria: a) being militant cyclo-activist; b) holding political office and c) developing citizenship projects in both public and private management. From the phenomenological-hermeneutic methodology emerged units of meaning 'The cycling activist movement organization', 'educational processes experienced for fostering bicycle culture' and 'planning of public policy' resulting in the category 'urban cycling as sustainable active mobility'. We consider phenomenon bicycling represents the need to value human at scale coexistence in road traffic with potential for political transformation in city planning.